A chitosan-based multifunctional hydrogel containing in situ rapidly bioreduced silver nanoparticles for accelerating infected wound healing. Issue 13 (8th March 2022) - Zhao, Fengxin; Liu, Yifan; Song, Tao; Zhang, Bin; Li, Dongxiao; Xiao, Yumei; Zhang, Xingdong
Abstract : A double-crosslinked hydrogel with injectability, self-healing capability, stability, and antibiosis was developed. Silver ions were in situ bioreduced to AgNPs rapidly and uniformly at the same time as the formation of hydrogels. Abstract : Generally, bacterial infection seriously hinders the wound healing process, so it is crucial to safeguard the wound from severe infection. Besides, multifunctional hydrogel dressings (self-healing, injectable, antibacterial and adaptable) seem to be conducive to meet the needs of wound healing. Here, a double-crosslinked multifunctional hydrogel (COC hydrogel) based on quaternized chitosan, methacrylate anhydride-modified collagen and oxidized dextran was developed. The double-crosslinked network improved the stability of the hydrogel while not destroying the functionality of the Schiff base bond. More importantly, silver ions were rapidly in situ bioreduced to silver nanoparticles (AgNPs) during the formation of the COC hydrogel, which can essentially avoid the dispersion and agglomeration problems. The obtained COC@AgNP hydrogel had good biocompatibility compared with that loaded with silver ions and excellent antibacterial properties compared with that loaded with the same amount of commercial AgNPs. In vivo results indicated that the COC@AgNP hydrogel accelerated the healing process of infected full-thickness skin defects through anti-infection, anti-inflammation, stimulating collagen deposition, and promoting the formation of epithelia and blood vessels. Collectively, the COC@AgNP hydrogel has good potential for clinical infected wound dressing applications.